P123 The IFN type I gene expression in a cardiovascular disease continuum of rheumatoid arthritis. (21st February 2018) - Burska, AN; Harrison, G; Hensor, EM; Bissell, L-A; Fent, G; Sadreev, I; El Sherbiny, YM; Donica, H; Vital, EM; Plein, S; Buch, MH
Abstract : Introduction: Rheumatoid Arthritis (RA) patients have a prominent increase in cardiovascular (CV) comorbidity not fully explained by traditional risk factors. 1 Interferons type 1 (IFN-1) have been associated with premature CV disease (CVD) in SLE 2 and are implicated in several aspects of atherosclerosis and acute coronary syndromes. 3 In RA a subpopulation of patients also display an IFN-1 signature in the blood, 4 which is associated with response to biologics. The IFN- 1 signature association with CVD in RA remains unclear. Objectives: To analyse expression of interferon type 1 response genes (ISGs) along a CVD continuum in patients with RA using a well phenotyped cohort of RA patients whereby cardiovascular changes were assessed by Cardiac Magnetic Resonance Imaging (CMR). Methods: PBMCs samples from 60 RA patients (mean (90% CI)) age 62.4 (60.2, 64.6)y.o, sex F/M 42/18, disease duration 153.3 (121.3, 185.2) mths and n=18 healthy controls (HC); age 42 (37.8, 46.0) y, F/M 12/6 were obtained. RA patients were stratified based on CMR into: no CVD (RA CMRneg n=13) and abnormal CMR (RA CMRpos n=26), and RA with clinical CVD (no CMR, defined as history of cerebrovascular disease or ischaemic heart disease) (RA CVD n=21). qPCR of ISGs was performed using TaqMan Gene Expression Assays on Biomark (Fluidigm). Factor scores were created using the set of 51 genes measured in 78 subjects. Results: All routinely used biomarkers were associated with RA diagnosis (ACPA, RF, TJC, SJC, CRP, DAS28). Total cholesterol and LDL levels were higher in RA than in HC group (p=0.051 and p=0.015). Three IFN-1 scores were present in the dataset (IFN Score 1, 2 and 3) and were composed of 19, 21 and 7 genes respectively. IFN-1 score 2 showed significant differences between HC and RA CMRpos groups (mean difference and 90% CI: 0.52 (0.09, 0.96)) and HC and RA CVD (0.57 (0.10, 1.03)) as well as all RA patients with CVD (CMRpos and RA CVD) ((0.54 (0.16, 0.93); p<0.05 for all comparisons). IFN-1 Score 3 showed trend for a difference between RA CMRneg and CMRpos patients (0.37 (0.03, 0.70); p=0.071). There was no statistical difference between HC and RA CMRneg groups. Conclusions: An IFN-1 score 2 emerged as a possible factor characterising progression along a CVD continuum in RA patients, from no CVD to subclinical and clinical CVD; also distinguishing between HC and RA with subclinical and clinical CVD. These results warrant further evaluation in a larger cohort to confirm the findings. References: . Kaplan MJ. Curr. Opin. Rheumatol2006;18(3):289–297. . Somers EC, et al. PloS One2012;7(5):e37000. . de Winther MPJ. Arterioscler. Thromb. Vasc. Biol2016;36(2):217–218. . van der Pouw Kraan TC, et al. Ann. Rheum. Dis2007;66(8):1008–1014. Disclosure of interest: None declared